THE EFFECT OF LIQUIDITY, ASSET STRUCTURE, AND COMPANY SIZE ON CAPITAL STRUCTURE WITH COMPANY ROA AS INTERVENING VARIABLES IN PLANTATION SUB SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Danar Irianto; Ridho Tanso Rikalmi (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2025)
The aim of this research is to empirically confirm the impact of Liquidity, Asset Structure, and Firm Size on Capital Structure where Return on Assets (ROA) would serve as the mediator. Here, liquidity specifies the company's capability to meet short-term obligations, asset structure and firm size specify the composition and range of the firm's business that can influence financing. This research uses all listed firms in the agricultural sub-sector on the Indonesia Stock Exchange (IDX) for the period 2016-2019, with 19 observations. Parametric and non-parametric statistical techniques are employed for data analysis to examine the study variables. The steps to the analysis include the use of normality tests to confirm the appropriate distribution of data, and hypothesis testing to verify the variable relationships. Additionally, this research includes the results of the hypotheses tests and employs Path Analysis to ascertain the pathways of influence of the variables. The outcomes of this research will be in a position to provide better understanding of the determinants of the capital structure of companies operating in the agricultural sector, as well as the role of ROA as an intervening variable in such a relationship. These findings are anticipated to serve as a guide for company management in decision-making regarding funding policy and asset management. Keywords: liquidity, return on assets, asset structure, capital structure, company size.